The toxicity of extracts from Callicarpa candicans (Burm) Hochr. of the family Verbenaceae against brine shrimp (Artemia salina L.). - Espino, Samuel S.
The study is about the toxicity of the extracts from the of Callicarpa candicans (Burn) Hochr. Family Verbenaceae. It seeks to answer whether the of the plant show toxicity as reported and what were the probable compounds responsible for the toxicity. The of the plant were used for the study and were screened for the presence of alkaloids, saponins and tannins. The tested negative for alkaloids and positive for saponins and tannins. Four solvents were used to extract the compounds from the namely: Petroleum ether, methanol, dichloromethane, and ethanol. For the crude petroleum ether extract using 90.0023 grams of the sample, 6.0199 grams of the crude extract was obtained. For methanol, 30.0009 grams yielded 3.2942 grams of the crude extract, for dichloromethane, using 30.0007 grams of the sample, 1.2580 grams of crude extract was obtained and for ethanol, 30.0015 grams of the sample yielded 2.6552 grams of the crude extract., To test for toxicity of the extracts, the Brine Shrimp Bioassay for Toxicity was used. Results showed that the dichloromethane extract has the lowest LC50 equal to 215 ug/ml. The dichloromethane extract was subjected to column chromatography and six fractions were obtained. Thin Layer Chromatography was used to determine what classes of phytochemicals were present in the dichloromethane extract. The different fractions obtained from the DCM extract were again subjected to the assay for toxicity. The result of the bioassay for the different fractions showed that the third fracttion with an LC50 of 80 ug/ml has the lowest LC50. TLC showed that the DCM fractions contain saponins, tannins, phenols, and anthraquinones and/or coumarins.